‘We are all time poor’ Is routine nutrition screening of older patients feasible? - Hamirudin, Aliza Haslinda; Charlton, Karen; Walton, Karen; Bonney, Andrew; Albert, George; Hodgkins, Adam; Potter, Jan; Milosavljevic, Marianna; Dalley, Andrew (Royal Australian College of General Practitioners, 2013)
Background: Despite clinical guidelines that recommend routine nutrition screening of older patients, this does not generally occur in the Australian general practice setting. This study aimed to identify perceived barriers and opportunities to implementing nutrition screening of older people in general practice. Methods: Twenty-five in-depth individual interviews were conducted with general practitioners, general practice registrars and practice nurses. Interviews were audio-recorded, transcribed verbatim and analysed thematically. Observations were performed to identify opportunities to conduct nutrition screening within general practice workflow. Results: The primary identified barrier to screening related to time constraints, which was further validated by the observational component of the study. The main opportunity for screening was seen to be within the existing Australian Government Medicare Benefits Schedule Primary Care Item, ‘Health assessment for people aged 75 years and older’. Discussion: Incorporation of a validated and short nutrition screening instrument into the existing Health assessment was identified as the most feasible way to encourage the uptake of nutrition screening in general practice.